Genocias ir rezistencija Nr. 14(2) - Bubnys, Arūnas; Strelcovas, Simonas; Kšanytė, Raminta; Matulytė, Margarita; Briedienė, Ramunė; Starkauskas, Juozas (Genocidas ir rezistencija, 2003)
Pilnas leidinys (nuskenuota popierinė versija)